Interactive Multimedia Based Long Jump Athletic Learning During the Covid-19 Pandemic at FIK UNIMED - Suharjo Suharjo; Imran Akhmad; Faridz Ravsamjani; Dicky Edwar Daulay (UNIB Press, 2022)
Jump numbers are included in the classification of skill types that are acycliccombined. This means that there is a cyclic movement which is then continued with the acyclical movement so that it can take advantage of the part method (partmethod) and the whole (whole method). It provides an understanding of audio as something related to reception through sound and hearing. Visual is something related to the eye or vision, props, can be seen and witnessed. It can be said that audio visuals are